Strategi Pengembangan Usaha UMKM di Era Digital: Studi Kasus Havana Collection dengan Pendekatan SWOT–QSPM - Juliana, Juliana; Imsar, Imsar; Daulay, Aqwa Naser (Universitas Proklamasi 45, 2025)
This study examines business development strategies for a small and medium enterprise (Havana Collection) in the digital era and prioritizes actionable initiatives using a SWOT–QSPM approach. Internal and external factors were mapped through field observations and document review; weighted scores were computed with IFAS/EFAS, strategic alternatives were formulated via SWOT, and priorities were determined using the Quantitative Strategic Planning Matrix. The firm’s IFAS and EFAS totals indicate a relatively favorable external context (IFAS ≈ 2.56; EFAS ≈ 2.71). QSPM highlights an SO-led pathway: intensifying digital marketing—including paid ads, creator collaborations, and affiliate programs—emerges as the top priority, while product development and market expansion serve as supportive moves. Managerially, the roadmap emphasizes content capability and performance analytics, sequencing quick wins while strengthening core processes. The study demonstrates how a compact, evidence-based framework translates qualitative factor mapping into an implementable priority list for SME growth in the digital landscape.